Development Of Physics Learning Devices Based On Student Learning Style - Noriwita, Indah Resty; Zamri, Rifki; Islami, Nur (Proceedings of the UR International Conference on Educational Sciences, 2018)
Teachers understanding of the diversity of student learning styles in a classroom can improve the quality of learning. Therefore, research has been done and physics learning tools based on student learning style have been developed successfully. The aim of this study is to produce the valid of physics learning devices based on student learning style of temperature and heat material at X SMA. The device development method used Research and Development (R & D) method. The Steps of R & D methods start from identifying potentials and problems, collecting data, product design, design validation by the professor of research methodologies, design revisions and final product trials. The validation result of the learning device validity instrument is the source of the research data. The percentage of validation results of RPP, LKS, media, and test of learning result in sequence was 88.14%; 75.50%; 87.24%; and 89.09% The percentage of such validation results is categorized as very high with an average score of 83.99%. The average number indicates that the developed learning device is valid.